Digital scaffold supporting dialogue and acquisition of academic language related to argumentation during online inquiry - Murphy, Victoria (2016)
In the 21st century collaboration and the use of digital environments have been recognised as key areas of classroom ecology. Dialogue in particular has been highlighted as an important part of collaboration in many studies. This thesis aims to investigate whether digital scaffolding can play a supporting role in improving the quality of dialogue between students working in pairs. Data was collected during a task, where a class of 16-17 years old students from the US were asked to find information to be used to compose an argumentative essay. Students used a digital scaffolding tool to support consideration of multiple perspectives, as well as evaluate source reliability and credibility. Dia-logue of 4 dyads was examined by studying episodes of exploratory, cumulative and disputational talk. Episodes of different stages of online inquiry were also identified. The location of different types of episodes while using the digital tool was noted. Analysis of when utterances of key academic terms occurred was also employed to investigate digital scaffolding’s potential influence on acquisition of language related to argumentation. The digital scaffolding used during this study was found to support exploratory talk when identifying problems, and evaluating source quality during online inquiry. Evidence was also obtained to support the view that digital scaf-folding could prompt acquisition of academic terms related to argumentation. Analysis here supports the link between dialogue quality and the ecological environment of educational tasks. However, many factors, such as the relationship dynamic of the individuals in the pair, remain ripe for future research.